ENVIRONMENTAL IMPACTS OF RADIOACTIVE ISOTOPES IN INDUSTRIAL APPLICATIONS AND THEIR MITIGATION STRATEGIES? - Samridhi Dhingra (International Educational Journal of Science and Engineering, 2025)
This paper examines the environmental impacts of using radioactive isotopes in various industrial applications and evaluates the strategies available to mitigate these impacts. Radioactive isotopes are widely employed in sectors like medicine, agriculture, and industrial processing, and while they provide significant advantages, they also present several environmental risks. The study reviews existing literature to identify the potential hazards posed by isotopes such as Cesium-137, Cobalt-60, and Americium-241 and discusses the pathways through which these isotopes can affect ecosystems. Finally, it outlines effective mitigation strategies, such as containment measures, decontamination techniques, and regulatory frameworks, to minimize the adverse environmental effects.